Never have I ever - Shepard, Sara, 1977- (New York : HarperTeen, 2011)
When Emma Paxton steps into the life of her long-lost twin Sutton to solve her murder, she finds new suspects at every turn, while Sutton looks on from her afterlife.
Keywords: Twins -- Juvenile fiction; Sisters -- Juvenile fiction; Murder -- Juvenile fiction; Dead -- Juvenile fiction; Twins -- Fiction; Sisters -- Fiction; Murder -- Fiction; Dead -- Fiction; Mystery and detective stories; Mystery fiction